Tendințe recente în constituirea clasei sociale mijlocii în România - Mărginean, Ioan (Calitatea Vieții, 2011)
In this paper, recent trends in the formation of middle class are analysed by taking into consideration the dynamics of the number of employees in all occupational groups (ISCO codes) that stimulates middle class development. These are nonmanual occupations (management, professionals, public servants, supervisors, occupations in services and commerce). The analysis refers to 2005–2009, and is a follow-up of the one included in the volume “Formation of middle class in Romania” (authors Larionescu, Mărginean, Neagu, Editura Economică, 2006, CNCSIS funding). The research results show that the number of high education graduates increased (from 125 000 in 2007 to 233 000 in 2008), suggesting, on the one hand the availability of human resources to get involved in nonmanual activities. On the other hand, even if the activity rate of this category grew to a certain extent, the current economic crisis affects negatively the dynamics of employment, even more in some key-groups of middle class, like business owners and entrepreneurs. This group decreased 11% in 2005–2009, from 140,000 to 125,000. In the same time, the layoffs and the closing of hiring in the public sector determined a diminishing of employment rates in some sectors of the economy. In the following years it is expected the growth of middle class to be modest.